2X+(3-X)=6

Simple and best practice solution for 2X+(3-X)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2X+(3-X)=6 equation:


Simplifying
2X + (3 + -1X) = 6

Remove parenthesis around (3 + -1X)
2X + 3 + -1X = 6

Reorder the terms:
3 + 2X + -1X = 6

Combine like terms: 2X + -1X = 1X
3 + 1X = 6

Solving
3 + 1X = 6

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 1X = 6 + -3

Combine like terms: 3 + -3 = 0
0 + 1X = 6 + -3
1X = 6 + -3

Combine like terms: 6 + -3 = 3
1X = 3

Divide each side by '1'.
X = 3

Simplifying
X = 3

See similar equations:

| x^2*100=x^2+144 | | 3x+3=3x-11 | | 5x+34=14x-6 | | u^2-56=0 | | 2x^2+2y^2-8x+5y+3=0 | | z^2-56=0 | | 4(2n-5)=3n+2 | | ln(4x+2)=ln(7x-10) | | -7x^2+6+2x-12-9x^2= | | -35=7y+4(y-5) | | 7x+12=6x+14 | | x+14=6x-21 | | 2cos^2x+3cosx-5=0 | | 6x+2(-3x-2)=-4 | | 12*8-13=12x | | 11s+17(1870-s)= | | -2(-3v+y)+4(-y-5v)= | | 3x+5+7x=2*10x | | 15+-3y=13 | | 3x^3=15x^2 | | 48n^2+12n=0 | | 8y-5=35 | | -11+13x=4x | | 12-x=9x | | 2(x+10)+6=50 | | 7+8-12=3x | | 3x+25=8x-10 | | 9x^8-8x^9-0.75=0 | | 0.0225x=15 | | -4y-y=-6150 | | 8(y-4)=-2y-2 | | 144s=180(n-2) |

Equations solver categories